RearType: Text Entry Using Keys on the Back of a Device - Scott, James; Izadi, Shahram; Rezai, Leila Sadat; Ruszkowski, Dominika; Bi, Xiaojun; Balakrishnan, Ravin (Proceedings of MobileHCI 2010, 2010)
RearType is a text input system for mobile devices such as Tablet PCs, using normal keyboard keys but on the reverse side of the device. The standard QWERTY layout is split and rotated so that hands gripping the device from either side have the usual keys under the fingers. This frees up the front of the device, maximizing the use of the display for visual output, eliminating the need for an onscreen keyboard and the resulting hand occlusion, and providing tactile and multi-finger text entry – with potential for knowledge transfer from QWERTY. Using a prototype implementation which includes software visualization of the keys to assist with learning, we conducted a study to explore the initial learning curve for RearType. With one hour’s training, RearType typing speed was an average 15 WPM, and was not statistically different to a touchscreen keyboard.